Overconfident People Are More Exposed to "Black Swan" Events: A Case Study of Avalanche Risk - Nicolao Bonini; Stefania Pighin; Enrico Rettore; Lucia Savadori; Federico Schena; Sara Tonini; Paolo Tosi (Institute for the Study of Labor (IZA), 2015)
Overconfidence is a well-established bias in which someone's subjective confidence in their own judgments is systematically greater than their objective accuracy. There is abundant anecdotal evidence that overconfident people increase their exposure to risk. In this paper, we test whether overconfident people underestimate the probability of incurring an avalanche accident. An avalanche accident is a typical "black swan" event because it has a low probability of occurring but has potential dramatic consequences. To test whether the overconfidence bias affects the decision of backcountry skiers to go on a ski trip under different levels of avalanche risk, we measured individual cognitive traits and then used a random effect logit model to measure their effects on the probability to take the tour, by controlling for other observable characteristics of the respondent. We show that 1) overconfidence is widespread even in our sample and 2) practitioners who are more prone to overestimate their knowledge are also more likely to take the risk associated with a ski trip exposed to avalanche danger. This suggests that overconfident people are more exposed to black swan events.
Keywords: D83; D84; C2; 330; cognitive bias; risky decision; backcountry skiing; measurement errors; logit model